Mechanical and thermal properties of a novel Spinifex Littoreus fiber reinforced polymer composites as an alternate for synthetic glass fiber composites. (1st March 2021) - S, Milan; Christopher, T; Manivannan, A; Mayandi, K; Jappes, J T Winowlin
Abstract: The usage of natural fiber reinforced composite is large in engineering applications due to the presence of high extensive properties and economy. This paper aims at presenting a new fiber, its characteristics, and composite in a polymeric matrix empowering the generation of less weight composites for load conveying applications. Spinifex Littoreus Fiber (SLF) is a genus of perennial coastal plants in the grass family. The comprehensive characterization that includes physical analysis, chemical analysis, thermal analysis, mechanical and microstructural characteristics have been carried out on the fiber. The effect of fiber weight percentage was studied from the point of view of the mechanical properties of the compression moulded Spinifex Littoreus Fiber Composites (SLFC). Mechanical properties attained at 40 wt% of fiber content were better. In addition to more fiber, it tends to cause inadequate bonding among the matrix and fiber, resulting in a decrease in mechanical performance. The specific properties of SLFC polymer composites are comparable to those of the glass fiber composite. This makes SLFC composite as an alternate lightweight material. SEM was performed for a study of the interfacial mechanism.